A new genus of Pulaeini (Acari: Prostigmata: Cunaxidae) from South–East Asia - Kalúz, Stanislav; Ermilov, Sergey G. (Zootaxa, 2019)
A new genus Lepidocunaxoides gen. nov., with the type species Lepidocunaxoides robustus sp. nov. (Acari: Prostigmata, Cunaxidae), is described and figured from Vietnam. The general characters of the genus Lepidocunaxoides gen. nov. within the tribe Pulaeini include: palp femurogenu with 6 setae; palp tibiotarsus with 5 setae; setal formula for telofemora I–IV 5-5-4-3 sts; setae f2 absent. It differs from related genera of the subfamily Cunaxoidinae by its paired ventral plates resembling butterfly wings, separating the sternal plate from fused coxae II–IV, by three paired platelets around the genital plates, and by the basifemora I–IV setal formula 3-5–3-2. An undated identification key to the tribes and genera of Cunaxoidinae is provided.